Close Reading a Close Reading: Revisiting Mystery House in Mechanisms - Aycock, John (Loading)

(untitled) (Canadian Game Studies Association, 2025)
Mystery House is a game that was released in 1980 for the Apple II computer. It was the first text adventure game known to be illustrated and was the game design debut of celebrated game designer Roberta Williams. The landmark 2008 book Mechanisms: New Media and the Forensic Imagination performed a close reading of a Mystery Housefloppy disk, and in this paper I turn a critical eye to this previous work. My close reading of Mystery House’s earlier close reading reveals a number of problems, which I use as a vehicle to highlight a notable and important technical gap in game studies scholarship, and argue for an inclusive approach to advancing the field.